MOISTURE RELEASE OF TROPICAL PEAT SOILS AS DECREASING WATER TABLE - Ahmad Kurnain (TROPICAL WETLAND JOURNAL, 2015)
Hydro-physics of peat soils varied with their peat decomposition degree. One of the important hydro-physics is ability of the peat soil to release water as decreasing water table. Potential of water availabilty to crop growth is evidently related to this behaviour. The present study was conducted to understand modes of moisture release of peat soils as decreasing water table. Water tables were simulated using a hanging column method. The water table was arranged at levels of 0, 10, 20, 30, 50, and 100 cm below peat column surfaces. Potential of moisture release or in oppositely potential of moisture retention could be modelled with the 3 parameter equation. Highly decomposed peat characterized by higher bulk density and lower total porosity stored less water but retained more water.